Analysis of the Implementation of PSSI Football Curriculum Age 14-17 Years in Soccer Schools in Gorontalo Province - Maisal Nento; Sulaiman Sulaiman; Mugiyo Hartono (STKIP Muhammadiyah Kuningan, 2023)
The purpose of this research is to analyze how the Communication System, Resources, Attitudes and Commitment, and Executing Organizations in the implementation of the PSSI football curriculum aged 14-17 years at football schools in Gorontalo Province. The method used in this study uses a qualitative approach with a case study research design. Data collection was carried out by observation, interview and documentation methods. Data and data sources come from primary data and secondary data. The primary data are football school administrators, coaches, athletes, Asprov and Askab. Secondary data consists of football school documents. The results of this study show that communication systems, resources, attitudes and commitments, as well as implementing organizations in the implementation of the PSSI soccer curriculum aged 14-17 years at football schools in Gorontalo province have strengths, weaknesses, opportunities, and threats. (Threats) which vary, especially in human resources. So it can be concluded that all aspects observed are not entirely good, because each aspect still has deficiencies that affect the implementation of the PSSI football curriculum aged 14-17 years at football schools in Gorontalo Province.